Identification of the Potential For Tourism in Lumbung Village, West Selemadeg District, Tabanan Regency Bali - Krismawintari, Ni Putu Dyah; Tejasukmana, IWK; Patni, Ni Luh Putu Suarmi Sri; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
Indonesia has a diversity of nature, culture, and customs which are a tourist attraction. It is important to know the potential of an area so that it can be optimized to improve the welfare of the local community and preserve culture. The successful development of a region requires the role of various parties and government support. The tourism village is one of the efforts to implement sustainable tourism development based on the community. Lumbung Village is one of the villages in West Selemadeg Subdistrict, Tabanan Regency, Bali, which has natural and cultural beauty that is not yet known by the wider community. It is necessary to identify a potential tourist attraction in Lumbung Village. Social studies humanities are exploratory-qualitative to find reduced and analyzed using analysis 4A tourist destinations (power Pull/attraction, access/accessibility, facilities /amenities, and institutional support /ancillary. In this study, the reduction is based on the concept of 4A development of tourist destinations and Tourism village criteria as a basic instrument for tourism village development. Determination of research conclusions based on the final score or the instrument based on the results of observations and interviews on pre-criteria designed Based on the results of observations in Lumbung Village, Selemadeg District, Tabanan Regency Bali, the score was 195 included in the very criteria so that the village of Lumbung has the potential to become a tourist attraction.